Allergic rhinitis and immunoglobulin deficiency in preschool children with frequent upper respiratory illness - Sudawan Siriaksorn (2018)
Background: Frequent upper respiratory illness (URI) is a common problem in preschool children. Allergic rhinitis and immunoglobulin (Ig) deficiency are usually suspected as underlying etiologies. Objective: To determine the prevalence of allergic rhinitis and Ig and IgG subclass deficiency in preschool children with frequent URI. Methods: Two thousand eight hundred and seventy-six questionnaires were distributed to the parents of children aged 3-6 years in 24 kindergartens. Firstly, they determined the frequency of URI in the previous year and secondly the prevalence of rhinitis according to the International Study of Asthma and Allergies in Childhood (ISAAC) questionnaire. The skin prick test (SPT) was performed and serum Ig and IgG subclasses were measured in children with frequent URI (>10 episodes per year). Allergic rhinitis was diagnosed when the child had had rhinitis in the previous 12 months and positive SPT for at least 1 aeroallergen. Results: Two thousand three hundred and one questionnaires (80.01%) were returned. Ninetyfour out of 219 children with frequent URI participated in the study. The prevalence of allergic rhinitis in the participants was 42.55%. Exclusive breastfeeding for at least 6 months had a protective effect, while paternal history of rhinitis was a risk factor. All participants had normal serum IgG, IgA, IgM and IgG subclass levels for age. Conclusion: The prevalence of allergic rhinitis in preschool children with frequent URI in our study was 42.55%. Allergic rhinitis should be considered if they have a family history of allergic rhinitis. Immunoglobulin deficiency was not found in our study.